A methyl-shield strategy enables efficient blue thermally activated delayed fluorescence hosts for high-performance fluorescent OLEDs. Issue 7 (19th May 2021) - Ran, You; Yang, Ge; Liu, Yang; Han, Weiguo; Gao, Ge; Su, Rongchuan; Bin, Zhengyang; You, Jingsong
Abstract : A novel methyl-shield strategy has been developed to design ideal TADF hosts for achieving an ultra-high EQE of 32.3%, which represents the first report of the EQE reaching above 30% in TSF-OLEDs. Abstract : Here, we report a novel methyl-shield strategy to design ideal TADF hosts for the improvement of the performance of TSF-OLEDs. The methyl group on the xanthone acceptor acts like a shield to protect the luminance center from close intermolecular hydrogen bonding with adjacent molecules, thus alleviating exciton quenching, and meanwhile the small size of the methyl group almost does not disturb the π–π stacking between acceptors, thus maintaining fast electron-transport pathways. d MeACRXTO having two methyl shields is exploited as the host to achieve a record-high EQE of 32.3%, which represents the first report of an EQE above 30% in TSF-OLEDs.